2018
DOI: 10.2174/1570180814666170823161318
|View full text |Cite
|
Sign up to set email alerts
|

Topical Formulations and Intradermal Injections of Tranexamic Acid in the Treatment of Hyperpigmentation - A Review

Abstract: Background: The anti-plasmin activity of Tranexamic Acid (TA) is considered to be the main mechanism of hypopigmentation. Several studies have found TA to be effective for both oral and topical application. When used to lighten stains, TA is effective even at low concentrations, ideally in the range of 2 to 5%. Increasing the duration of treatment is more effective than increasing the concentration of TA: Higher concentrations of TA (> 5%) do not improve the effect but rather cause irritation. The TA formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Tranexamic acid (TA, trans-4-aminomethylcyclohexanecarboxylic acid) is a synthetic amino acid which demonstrates anti-hemorrhagic activity and is used to treat bleeding in various origins (Acidum tranexamicum, medicine EXACYL). [1][2][3][4][5] However, during the course of treatment using oral TA, it was observed that administration also yielded whitening effects. 1,3,[6][7][8][9][10][11][12][13][14] Studies have shown that both oral administration and topical application of TA is effective at decreasing pigmentation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tranexamic acid (TA, trans-4-aminomethylcyclohexanecarboxylic acid) is a synthetic amino acid which demonstrates anti-hemorrhagic activity and is used to treat bleeding in various origins (Acidum tranexamicum, medicine EXACYL). [1][2][3][4][5] However, during the course of treatment using oral TA, it was observed that administration also yielded whitening effects. 1,3,[6][7][8][9][10][11][12][13][14] Studies have shown that both oral administration and topical application of TA is effective at decreasing pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, during the course of treatment using oral TA, it was observed that administration also yielded whitening effects. 1,3,[6][7][8][9][10][11][12][13][14] Studies have shown that both oral administration and topical application of TA is effective at decreasing pigmentation. 3,[15][16][17][18][19][20][21] In addition, the European Cosmetics Directive safety report does not indicate any health risks related to the superficial use of tranexamic acid for cosmetic purposes 1,3 ; however, topical application should be safer, due to the lack of systemic absorption.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations